Vacant Time Transformed: Exploring Student Activities Before and During Covid-19 Pandemic - Diaz, Joemar G. (Future Science / FSH-PH Publications, 2025)
Time is valuable, and vacant is essential for students’ relaxation and productivity. Before the pandemic, students spent their free time on social and extracurricular activities. However, COVID-19 disrupted education and altered how they used their vacant hours. This study explored students' activities during their school vacant time before and during the pandemic. It specifically aimed to (1) identify students' activities before the pandemic, (2) identify their activities during the pandemic, and (3) determine whether there was a significant difference between these activities. A descriptive quantitative analysis was used to interpret data from 257 senior high school students at Saint Francis of Assisi College – Las Piñas Campus. Weighted Mean and the Paired-Samples T-test were employed for data analysis. Findings revealed that before the pandemic, students primarily spent their vacant time listening to music, conversing with friends, and surfing the internet. During the pandemic, listening to music and surfing the internet remained the most common activities. However, restrictions prevented students from playing adult games, attending sports events, and participating in scientific and cultural activities. A significant difference was found between students' activities before and during the pandemic. The study suggests that parents ensure stable internet access for their children, while teachers incorporate engaging activities involving social media. Future research should explore the impact of students’ personal activities on mental health during the pandemic.